(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2014)
Angiosarcoma is a rare and aggressive, malignant neoplasm of endothelial-cell origin. A primary angiosarcoma originating in the testicle is extremely rare, with only five previous cases reported in the current literature. We report a case of primary, pure angiosarcoma of the testis in a 63-year-old patient with no history of previous chemotherapy or radiation therapy. By histology, the tumor was a high-grade spindle cell neoplasm, arranged in sheets and poorly-formed vascular channels. The tumor cells were positive for vascular markers (CD31, CD34) by immunohistochemical staining. No evidence of a germ cell component was seen by morphology, immunohistochemistry, or molecular genetic studies. This finding is unique in that it is one of only three reported cases of primary angiosarcomas of the testicle without a germ cell precursor or component.